2009
DOI: 10.1176/ps.2009.60.12.1612
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Utilization and Its Costs for Depressed Veterans With and Without Comorbid PTSD Symptoms

Abstract: Patients with PTSD and depression had greater utilization of specialty mental health treatments and antidepressant medications and higher mental health care costs in the previous 12 months than depressed patients without PTSD. As military personnel return from Iraq, both VA and non-VA health care providers need to plan for an increase in outpatient mental health services and costs, particularly among depressed veterans who also have PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…The comorbidity of depression and disability in low-income older adults is high (11, 12) and increases the cost of healthcare in the U.S. These costs are largely due to the disabling effects of depression (13) and could be reduced if depression and the accompanying disability, were treated effectively (14–17). …”
Section: Introductionmentioning
confidence: 99%
“…The comorbidity of depression and disability in low-income older adults is high (11, 12) and increases the cost of healthcare in the U.S. These costs are largely due to the disabling effects of depression (13) and could be reduced if depression and the accompanying disability, were treated effectively (14–17). …”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have examined use among depressed veterans, with or without PTSD, and have found that those with comorbid PTSD and depression were more likely to seek mental healthcare and use those services with greater frequency than patients with depression alone. 22,23 There also may be health service use differences among those with comorbid PTSD and alcohol use disorders (AUD), although, to our knowledge, no studies to date have examined this question. Thus, to further delineate health services use patterns among OEF/OIF veterans with PTSD seeking care at the VA, we used a retrospective study to describe (1) mental health outpatient, mental health inpatient, primary care, and emergency care service use by gender and (2) rates of service use among those with depression and AUD within gender.…”
Section: Introductionmentioning
confidence: 99%
“…The list consists of four yes/no questions representing the PTSD symptom clusters reexperiencing, avoidance/numbing, and increased arousal. The PC-PTSD was originally developed in a Veteran Affairs (VA) primary care setting (Prins et al, 2004) and has been widely used in the U.S. army (e.g., Chan, Cheadle, Reiber, Unutzer, & Chaney, 2009;Gore, Engel, Freed, Liu, & Armstrong, 2008;Hoge, Auchterlonie, & Milliken, 2006;Milliken, Auchterlonie, & Hoge, 2007;Seal et al, 2008). To date, its diagnostic qualities have exclusively been studied within VA settings, showing high sensitivity and specificity values for cutoff scores 2 (sensitivity N.84; specificity N.70) and 3 (sensitivity N.75; specificity N.86) in this population (Bliese et al, 2008;Prins et al, 2004).…”
Section: Introductionmentioning
confidence: 99%